Concrete adhesion-resistant corrosion-resistant coating and preparation method thereof
By preparing a corrosion-resistant coating for concrete adhesion and corrosion resistance on the surface of aluminum and magnesium alloy templates, the problems of adhesion and corrosion in use of the template are solved, and efficient anti-adhesion and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411682973.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
Aluminum and magnesium alloy formworks face serious adhesion and corrosion of concrete during use, resulting in difficulty in mold release and damage to the formwork.
A corrosion-resistant coating with anti-concrete adhesion and corrosion resistance, including modified epoxy resin, modified curing agent, filler, nanoparticles loaded with corrosion inhibitors, leveling agent, defoaming agent, dispersing agent and solvent, is prepared by compounding technology and scraping technology, and curing at 60-80°C.
The anti-adhesion performance, mechanical durability and chemical stability of the coating are improved, and effective anti-adhesion and corrosion resistance to aluminum and magnesium alloy templates are achieved. The surface hardness of the coating reaches 5-6H, and the contact angle is above 116°. It can be soaked in the concrete simulation liquid for a long time without falling off.
Smart Images

Figure CN119505638A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of anti-adhesion coatings, and in particular to an anti-concrete adhesion and corrosion-resistant coating and a preparation method thereof. Background Art
[0002] Building formwork is the formwork and support for concrete pouring, and is a type of basic material used in large quantities in the construction industry. Modern high-rise buildings are mainly built with formwork to form the structural cavity required for the building, and then directly pour mortar concrete. After the concrete is completely solidified, the formwork is stripped off and the structural cavity of the upper layer is constructed again, and the cycle continues until completion.
[0003] In recent years, aluminum and magnesium alloy formworks have been rapidly popularized due to their advantages such as light weight, convenient operation, good construction quality, and labor cost savings, providing support for the construction industry to achieve green and high-quality development. However, aluminum and magnesium alloy formworks still face two major problems in actual use: adhesion and corrosion of concrete. The surface concrete has severe adhesion and is difficult to demold. Even if a release agent is used every time, the concrete adhesion is still very serious and requires regular treatment, which is time-consuming and material-consuming. Concrete is highly corrosive and corrodes aluminum and magnesium alloys severely, resulting in an uneven surface of the formwork and enriched corrosion products, which intensifies adhesion.
[0004] In order to reduce the concrete adhesion of aluminum and magnesium alloy formworks and enhance the corrosion resistance in high alkalinity and high humidity environments, it is necessary to prepare an anti-adhesion and corrosion-resistant coating on the surface of aluminum and magnesium alloy formworks. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an anti-concrete adhesion and corrosion-resistant coating, aiming to overcome the defects of severe concrete adhesion on the surface of aluminum and magnesium alloy formworks and difficulty in demoulding.
[0006] In addition, another object of the present invention is to provide a method for preparing a corrosion-resistant coating that resists concrete adhesion, aiming to solve the problem of severe concrete corrosion on the surface of aluminum and magnesium alloy formworks.
[0007] In order to achieve the purpose of the above invention, the present invention adopts the following technical solutions:
[0008] The anti-concrete adhesion and corrosion-resistant coating provided by the present invention comprises the following raw materials in parts by mass:
[0009] 30-50 parts of modified epoxy resin, 10-20 parts of modified curing agent, 10-20 parts of filler, 2-5 parts of nanoparticles loaded with corrosion inhibitor, 0.1-1 parts of leveling agent, 0.2-0.6 parts of defoaming agent, 0.2-0.6 parts of dispersant, and 30-50 parts of solvent.
[0010] Furthermore, the modified epoxy resin is prepared by the following method: 6-10g of bisphenol A epoxy resin is dissolved in 30mL of ethyl acetate and magnetically stirred at 60°C for 30 minutes, then 0.1-0.5mL of a fluorine-free silane coupling agent with a purity of 98% and 0.05-0.1mL of water are added, and the mixture is reacted at 60°C for 6-8 hours under stirring to obtain the modified epoxy resin.
[0011] Furthermore, the modified curing agent is prepared by the following method: 6-10g of fatty amine curing agent is dissolved in 20mL of ethyl acetate and magnetically stirred at 80°C for 45 minutes, then 0.3-0.6mL of perfluoro organic acid with a purity of 98% is added, and the mixture is reacted at 100°C for 4-6 hours under stirring to obtain the modified curing agent.
[0012] Furthermore, the chemical formula of the perfluoroorganic acid is: n F 2n+1 COOH.
[0013] Preferably, the filler includes a micron-sized fibrous filler and a nano-sized filler in a mass ratio of 1:3-2:3; wherein the micron-sized fibrous filler is one or two of glass fiber and silicon carbide fiber, and the size of the micron-sized fibrous filler is 5-20 μm; the nano-sized filler is two or more of zirconium oxide, white carbon black, air glass beads, and diatomaceous earth, and the size of the nano-sized filler is 20-50 nm.
[0014] Furthermore, the nanoparticles in the nanoparticles loaded with corrosion inhibitors are mesoporous silica nanoparticles, and the corrosion inhibitor is any one or two of sodium stannate, sodium citrate, sodium tripolyphosphate, carbon quantum dots, and cerium sulfate.
[0015] Furthermore, the nanoparticles loaded with corrosion inhibitor are prepared by the following method: 1 g of corrosion inhibitor is dispersed in 10 mL of DMF solution, magnetically stirred for 30 minutes, 1 g of mesoporous silica nanoparticles is added, and then the DMF solution containing the mesoporous silica nanoparticles is placed in a vacuum oven, vacuumed for 3 hours, and then placed under standard atmospheric pressure for 1 hour; this process is repeated three times to increase the loading amount of corrosion inhibitor in the mesoporous silica nanoparticles; finally, the solution obtained by repeating three times is centrifuged, washed, and dried at 60°C for 10 hours to obtain nanoparticles loaded with corrosion inhibitor.
[0016] Preferably, the solvent is prepared by adding 1%-4% by mass of ammonia water to a mixture of any two of butyl acetate, cyclohexanone and ethyl acetate, wherein the mass ratio of any two components in the solvent is 2:1-3:1.
[0017] Furthermore, the coating also includes a pigment, and the surface hardness of the coating reaches 5-6H, the surface is hydrophobic and the contact angle is above 116°, and in a laboratory cement curing peeling test, the adhesion area does not exceed 20% after 60 cycles, and the coating is immersed in concrete simulation liquid for 60 days without hollowing or falling off.
[0018] In addition, the present invention also provides a method for preparing a concrete adhesion and corrosion resistant coating, which is used to prepare the above-mentioned coating. The preparation method adopts the following operation process:
[0019] (1) Add filler, nanoparticles loaded with corrosion inhibitor, dispersant and 1 / 3 of solvent into a high-speed stirring kettle, add modified epoxy resin and 1 / 3 of solvent after stirring for 10 minutes, add leveling agent and defoamer after continuing stirring for 3 minutes, add modified curing agent and 1 / 3 of solvent after continuing stirring for 5 minutes, add pigment after 5 minutes, continue stirring for 3-10 minutes and then discharge;
[0020] (2) applying the coating prepared above onto a clean metal substrate using a scraper coating technique, with a coating thickness of 0.8-1.0 mm;
[0021] (3) The coating prepared above is cured at 60-80° C. for 3-10 hours to obtain a corrosion-resistant coating that is resistant to concrete adhesion.
[0022] Beneficial effects of the present invention:
[0023] (1) The modified epoxy resin, modified curing agent and filler in the present invention reduce the surface energy of the coating and improve the anti-sticking property, mechanical durability and chemical stability of the coating; the nanoparticles loaded with corrosion inhibitors achieve the continuous release of the corrosion inhibitors and improve the corrosion resistance of the coating; the ammonia water added to the solvent enhances the bonding strength between the coating and the substrate.
[0024] (2) The present invention adopts innovative compounding technology to start from corrosion resistance, anti-adhesion, mechanical durability, bonding force, surface energy and roughness, and adopts simple scraping technology to achieve the preparation of anti-adhesion and corrosion-resistant coating on metal surface. The coating surface hardness reaches 5-6H, the surface is hydrophobic, the contact angle is above 115 degrees, the bonding strength is high, it can be recycled for 60 cycles without falling off, and it can be immersed in concrete simulation liquid for 60 days without blistering or cracking. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0026] Figure 1 This is an electron microscope morphology image of the coating in Example 2 of the present invention.
[0027] Figure 2 This is a contact angle photograph of Example 4 of the present invention.
[0028] Figure 3 This is a diagram of the anti-concrete adhesion in Example 5 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In view of the two major problems of concrete adhesion and corrosion faced by aluminum and magnesium alloy formworks in actual use, the present invention provides an anti-concrete adhesion and corrosion-resistant coating and a preparation method thereof in order to reduce the concrete adhesion of aluminum and magnesium alloy formworks while also enhancing the corrosion resistance in high alkalinity and high humidity environments.
[0031] Based on this, the overall solution of the anti-concrete adhesion and corrosion-resistant coating provided by the present invention is as follows:
[0032] The anti-concrete adhesion and corrosion-resistant coating of the present invention comprises the following raw materials in parts by mass:
[0033] 30-50 parts of modified epoxy resin, 10-20 parts of modified curing agent, 10-20 parts of filler, 2-5 parts of nanoparticles loaded with corrosion inhibitor, 0.1-1 parts of leveling agent, 0.2-0.6 parts of defoaming agent, 0.2-0.6 parts of dispersant, 30-50 parts of solvent, and appropriate amount of pigment.
[0034] The present invention further describes in detail the various raw materials for the coating provided above.
[0035] The modified epoxy resin involved in the present invention is prepared by the following method: 6-10g of bisphenol A epoxy resin is dissolved in 30mL of ethyl acetate and magnetically stirred at 60°C for 30 minutes, then 0.1-0.5mL of a fluorine-free silane coupling agent with a purity of 98% and 0.05-0.1mL of water are added, and the mixture is reacted at 60°C for 6-8 hours under stirring to obtain the modified epoxy resin.
[0036] The modified curing agent involved in the present invention is prepared by the following method: 6-10g of aliphatic amine curing agent is dissolved in 20mL of ethyl acetate and stirred magnetically at 80°C for 45 minutes, and then 0.3-0.6mL of a perfluoro organic acid C with a purity of 98% is added. n F 2n+ 1COOH, react at 100℃ with stirring for 4-6 hours to obtain a modified curing agent.
[0037] The modification mechanism of the modified curing agent is as follows:
[0038]
[0039] The modified bisphenol A epoxy resin and modified curing agent in the coating are the main components of the coating, which are the source of the coating's wear resistance, hardness, toughness and hydrophobicity, and provide anti-adhesion. The silane coupling agent or perfluoro organic acid used for modification can couple with the epoxy resin body or curing agent without destroying the original performance, while significantly reducing the surface energy.
[0040] The fillers involved in the present invention include micron-sized fibrous fillers and nano-sized fillers in a mass ratio of 1:3-2:3; wherein the micron-sized fibrous fillers are one or two of glass fibers and silicon carbide fibers, and the size of the micron-sized fibrous fillers is 5-20 μm; the nano-sized fillers are two or more of zirconium oxide, white carbon black, air glass microbeads, and diatomaceous earth, and the size of the nano-sized fillers is 20-50 nm.
[0041] The nanoparticles in the nanoparticles loaded with corrosion inhibitors involved in the present invention are mesoporous silica nanoparticles, and the corrosion inhibitor is any one or two of sodium stannate, sodium citrate, sodium tripolyphosphate, carbon quantum dots, and cerium sulfate.
[0042] Furthermore, the nanoparticles loaded with corrosion inhibitor in the present invention are prepared by the following method: 1 g of corrosion inhibitor is dispersed in 10 mL of DMF solution, magnetically stirred for 30 minutes, 1 g of mesoporous silica nanoparticles is added, and then the DMF solution containing the mesoporous silica nanoparticles is placed in a vacuum oven, vacuumed for 3 hours, and then placed under standard atmospheric pressure for 1 hour; this process is repeated three times to increase the loading amount of corrosion inhibitor in the mesoporous silica nanoparticles; finally, the solution obtained by repeating the three times is centrifuged, washed, and dried at 60°C for 10 hours to obtain nanoparticles loaded with corrosion inhibitor.
[0043] Fillers can enhance the hardness and toughness of the coating, reduce defects generated during the resin curing process, and enhance corrosion resistance. Micron-sized fibrous fillers can provide protective support for nano-sized fillers in the coating to improve the mechanical durability of the coating. If the corrosion inhibitor is added directly to the epoxy resin coating, the corrosion inhibitor is likely to interact with the functional groups in the resin, thereby affecting its physical and mechanical properties. To this end, the corrosion inhibitor is loaded onto mesoporous silica nanoparticles and then added to the coating. In addition to acting as a filler, the nanoparticles loaded with corrosion inhibitors also release the corrosion inhibitors after being attacked by corrosive media to improve the corrosion resistance of the coating. The loaded corrosion inhibitors are adsorbed on the metal surface by means of electrostatic attraction, intermolecular forces and chemical bonds formed on the metal surface, or form a stable protective film with metal ions to prevent the coating from falling off at the damaged part, so as to enhance the corrosion resistance of the coating. In addition, the nanoparticles loaded with corrosion inhibitors promote the hardness and toughness of the coating and reduce the defects generated during the resin curing process.
[0044] The solvent involved in the present invention is prepared by adding 1%-4% ammonia water to a mixture of any two of butyl acetate, cyclohexanone and ethyl acetate, wherein the mass ratio of any two components in the solvent is 2:1-3:1.
[0045] The solvent can adjust the viscosity of the coating and the dispersibility and adsorption properties of the pigments and fillers. The addition of ammonia in the solvent provides a large number of hydroxyl groups for the coating, which enhances the bonding strength between the coating and the substrate. The proportion of the mixed solvent is selected according to the density and addition amount of the filler.
[0046] In addition, the leveling agent involved in the present invention enhances the fluidity of the coating during the preparation process, making it easier to form a film. The dispersant promotes the dispersion of fillers, nanoparticles loaded with corrosion inhibitors, and pigments, keeping the particles suspended. The defoamer can make the film wall of the bubble thinner, making it easier to break, solving the problem of coating foaming. The present invention also includes an appropriate amount of pigment, but the present invention does not limit the content of the pigment.
[0047] At the same time, the present invention also provides a method for preparing a concrete adhesion and corrosion resistant coating, which is used to prepare the above-mentioned coating. The preparation method adopts the following operation process:
[0048] (1) Add filler, nanoparticles loaded with corrosion inhibitor, dispersant and 1 / 3 of solvent into a high-speed stirring kettle, add modified epoxy resin and 1 / 3 of solvent after stirring for 10 minutes, add leveling agent and defoamer after continuing stirring for 3 minutes, add modified curing agent and 1 / 3 of solvent after continuing stirring for 5 minutes, add pigment after 5 minutes, continue stirring for 3-10 minutes and then discharge;
[0049] (2) applying the coating prepared above onto a clean metal substrate using a scraper coating technique, with a coating thickness of 0.8-1.0 mm;
[0050] (3) The coating prepared above is cured at 60-80° C. for 3-10 hours to obtain a corrosion-resistant coating that is resistant to concrete adhesion.
[0051] It should be noted here that high curing temperature can promote the cross-linking reaction between epoxy resin molecules, which will speed up the curing rate and increase the hardness. However, too high a temperature will lead to too fast curing, which will increase the stress inside the epoxy resin, causing the chemical bonds in the cured product to break, resulting in internal defects, affecting its toughness and reducing thermal stability. Low curing temperature will lead to slow curing rate and incomplete curing.
[0052] In the preparation method of the present invention, the filler and the nanoparticles loaded with the corrosion inhibitor that are first added can be evenly dispersed in the solvent under high-speed stirring, and the modified epoxy resin and one-third of the solvent, the modified curing agent and one-third of the solvent that are subsequently added can ensure that the solution has suitable viscosity and fluidity to form a homogeneous mixture with good dispersion.
[0053] Based on the technical solutions and technical principles provided above, the present invention provides specific embodiments 1-5 and comparative examples.
[0054] Example 1
[0055] The anti-concrete adhesion and corrosion-resistant coating comprises the following raw materials in parts by mass:
[0056] 50 parts of modified epoxy resin, 16 parts of modified curing agent, 16 parts of filler, 3 parts of nanoparticles loaded with corrosion inhibitor, 0.2 parts of leveling agent, 0.6 parts of defoaming agent, 0.6 parts of dispersant, 42 parts of solvent, and appropriate amount of pigment.
[0057] The epoxy resin modification operation is as follows: 10 g of bisphenol A epoxy resin is dissolved in 30 mL of ethyl acetate and magnetically stirred at 60° C. for 30 minutes, then 0.1 mL of 98% pure fluorine-free silane coupling agent and 0.05 mL of water are added, and the mixture is stirred at 60° C. for 6 hours to obtain a modified epoxy resin. The fluorine-free silane coupling agent used in this example is codenamed KH550.
[0058] The curing agent modification operation is as follows: 10g of fatty amine curing agent is dissolved in 20mL of ethyl acetate and stirred magnetically at 80℃ for 45 minutes, then 0.3mL of 98% pure perfluoro organic acid C is added. n F 2n+1 COOH, react at 100°C for 4 hours under stirring to obtain a modified curing agent.
[0059] The corrosion inhibitor loading operation is as follows: 1g of corrosion inhibitor is dispersed in 10mL DMF solution, magnetically stirred for 30min, and 1g of mesoporous silica nanoparticles is added. Subsequently, the DMF solution containing mesoporous silica nanoparticles is placed in a vacuum oven, vacuumed for 3h, and then placed under standard atmospheric pressure for 1h. This process is repeated three times to increase the loading amount of corrosion inhibitor in mesoporous silica nanoparticles. Finally, the solution obtained by repeating three times is centrifuged, washed, and dried at 60°C for 10h to obtain nanoparticles loaded with corrosion inhibitor.
[0060] The fillers are air glass microspheres, diatomaceous earth and glass fibers, wherein the mass ratio of glass fibers to air glass microspheres and diatomaceous earth is 1:2:1, and the size of the glass fibers is 5 μm, the size of the air glass microspheres is 20 nm, and the size of the diatomaceous earth is 30 nm. The nanoparticles loaded with corrosion inhibitors are mesoporous silica nanoparticles loaded with sodium tripolyphosphate and carbon quantum dots, and the mass ratio of sodium tripolyphosphate to carbon quantum dots is 2:1. The solvent is prepared by mixing butyl acetate and cyclohexanone and then adding ammonia water with a mass fraction of 1%. The mass ratio of butyl acetate to cyclohexanone is 2:1.
[0061] The preparation method of the anti-concrete adhesion and corrosion-resistant coating is as follows: fillers, nanoparticles loaded with corrosion inhibitors, dispersants and one-third of solvents are added to a high-speed stirring kettle, and after stirring for 10 minutes, modified epoxy resin and one-third of solvents are added, and after continuing to stir for 3 minutes, leveling agents and defoamers are added, and after stirring for 5 minutes, modified curing agents and one-third of solvents are added, and pigments are added after 5 minutes, and stirring is continued for 3 minutes to discharge the material. The prepared coating is scraped onto a clean metal substrate using a scraping technique, and the coating thickness is 0.8 mm. The prepared coating is cured at 60° C. for 6 hours to obtain an anti-concrete adhesion and corrosion-resistant coating.
[0062] In this example, the dispersant is one of triethylhexyl phosphoric acid and polyacrylamide, and the specific product models that can be used are: K-271, ZY-DP-1; the leveling agent adopts polyether modified polydimethylsiloxane solution, and the specific product models that can be used are: BYK-346, XYS-5313; the defoaming agent is an organic silicone complex, and the specific product models that can be used are: Z-2004, F-0103.
[0063] In addition, this example does not limit the content of the pigment.
[0064] Example 2
[0065] The anti-concrete adhesion and corrosion-resistant coating comprises the following raw materials in parts by mass:
[0066] 45 parts of modified epoxy resin, 15 parts of modified curing agent, 10 parts of filler, 2 parts of nanoparticles loaded with corrosion inhibitor, 0.3 parts of leveling agent, 0.3 parts of defoaming agent, 0.3 parts of dispersant, 50 parts of solvent, and appropriate amount of pigment.
[0067] The epoxy resin modification operation is as follows: 6 g of bisphenol A epoxy resin is dissolved in 30 mL of ethyl acetate and magnetically stirred at 60° C. for 30 minutes, then 0.5 mL of 98% pure fluorine-free silane coupling agent and 0.1 mL of water are added, and the mixture is stirred at 60° C. for 8 hours to obtain a modified epoxy resin. The fluorine-free silane coupling agent used in this example is codenamed KH560.
[0068] The curing agent modification operation is as follows: 8 g of fatty amine curing agent is dissolved in 20 mL of ethyl acetate and stirred magnetically at 80°C for 45 minutes, then 0.6 mL of 98% pure perfluoro organic acid C is added. n F 2n+1 COOH, react at 100°C for 6 hours under stirring to obtain a modified curing agent.
[0069] The corrosion inhibitor loading operation is as follows: 1g of corrosion inhibitor is dispersed in 10mL of DMF solution, magnetically stirred for 30min, and 1g of mesoporous silica nanoparticles is added. Subsequently, the DMF solution containing mesoporous silica nanoparticles is placed in a vacuum oven, vacuumed for 3h, and then placed under standard atmospheric pressure for 1h. This process is repeated three times to increase the loading amount of corrosion inhibitor in mesoporous silica nanoparticles. Finally, the solution obtained by repeating three times is centrifuged, washed, and dried at 60°C for 10h to obtain nanoparticles loaded with corrosion inhibitor.
[0070] The fillers are silicon carbide fiber, glass fiber, zirconium oxide, air glass microspheres and white carbon black, wherein the mass ratio of glass fiber, silicon carbide fiber, zirconium oxide, air glass microspheres and white carbon black is 2:2:3:1:1, and the size of the glass fiber is 20 μm, the size of the silicon carbide fiber is 10 μm, the size of the zirconium oxide is 20 nm, the size of the air glass microspheres is 30 nm, and the size of the white carbon black is 30 nm. The nanoparticles loaded with corrosion inhibitors are mesoporous silica nanoparticles loaded with cerium tripolysulfate, and the solvent is prepared by mixing ethyl acetate and cyclohexanone and then adding ammonia water with a mass fraction of 1%. The mass ratio of ethyl acetate to cyclohexanone is 2.5:1.
[0071] The preparation method of the anti-concrete adhesion and corrosion-resistant coating is as follows: fillers, nanoparticles loaded with corrosion inhibitors, and dispersants are added to a high-speed stirring kettle, and after stirring for 10 minutes, modified epoxy resin is added, and after continuing to stir for 3 minutes, leveling agent and defoaming agent are added, and after stirring for 5 minutes, modified curing agent is added, and after 5 minutes, pigment is added, and stirring is continued for 8 minutes to discharge the material; the prepared coating is scraped onto the metal substrate by scraping technology, and the coating thickness is 0.9mm; then the coating is cured in an oven at 70°C for 3 hours to obtain the anti-concrete adhesion and corrosion-resistant coating. The microscopic morphology of the coating can be found in Figure 1 ,exist Figure 1 Not only the fibrous structure of the coating can be seen, but also the granular structure.
[0072] In this example, the dispersant is one of triethylhexyl phosphoric acid and polyacrylamide, and the specific product models that can be used are: K-271, ZY-DP-1; the leveling agent adopts polyether modified polydimethylsiloxane solution, and the specific product models that can be used are: BYK-346, XYS-5313; the defoaming agent is an organic silicone complex, and the specific product models that can be used are: Z-2004, F-0103.
[0073] In addition, this example does not limit the content of the pigment.
[0074] Example 3
[0075] The anti-concrete adhesion and corrosion-resistant coating comprises the following raw materials in parts by mass:
[0076] 30 parts of modified epoxy resin, 14 parts of modified curing agent, 16 parts of filler, 3 parts of nanoparticles loaded with corrosion inhibitor, 0.6 parts of leveling agent, 0.4 parts of defoaming agent, 0.2 parts of dispersant, 35 parts of solvent, and appropriate amount of pigment.
[0077] The epoxy resin modification operation is as follows: 6 g of bisphenol A epoxy resin is dissolved in 30 mL of ethyl acetate and magnetically stirred at 60° C. for 30 minutes, then 0.3 mL of 98% pure fluorine-free silane coupling agent and 0.09 mL of water are added, and the mixture is stirred at 60° C. for 7 hours to obtain a modified epoxy resin. The fluorine-free silane coupling agent used in this example is codenamed KH560.
[0078] The curing agent modification operation is as follows: 8 g of fatty amine curing agent is dissolved in 20 mL of ethyl acetate and stirred magnetically at 80°C for 45 minutes, then 0.6 mL of 98% pure perfluoro organic acid C is added. n F 2n+1 COOH, react at 100°C with stirring for 5 hours to obtain a modified curing agent.
[0079] The corrosion inhibitor loading operation is as follows: 1g of corrosion inhibitor is dispersed in 10mL DMF solution, magnetically stirred for 30min, and 1g of mesoporous silica nanoparticles is added. Subsequently, the DMF solution containing mesoporous silica nanoparticles is placed in a vacuum oven, vacuumed for 3h, and then placed under standard atmospheric pressure for 1h. This process is repeated three times to increase the loading amount of corrosion inhibitor in mesoporous silica nanoparticles. Finally, the solution obtained by repeating three times is centrifuged, washed, and dried at 60°C for 10h to obtain nanoparticles loaded with corrosion inhibitor.
[0080] The fillers are diatomaceous earth, zirconium oxide, glass fiber and silicon carbide fiber, wherein the mass ratio of glass fiber, silicon carbide fiber, diatomaceous earth and zirconium oxide is 1:1:2:2, and the size of glass fiber is 10 μm, the size of silicon carbide fiber is 20 μm, the size of diatomaceous earth is 20 nm, and the size of zirconium oxide is 50 nm. The nanoparticles loaded with corrosion inhibitors are mesoporous silica nanoparticles loaded with sodium citrate and carbon quantum dots, and the mass ratio of sodium citrate to carbon quantum dots is 1:1. The solvent is prepared by mixing butyl acetate and ethyl acetate and then adding ammonia water with a mass fraction of 1%. The mass ratio of butyl acetate to ethyl acetate is 3:1.
[0081] The preparation method of the anti-concrete adhesion and corrosion-resistant coating is as follows: fillers, nanoparticles loaded with corrosion inhibitors, and dispersants are added to a high-speed stirring kettle, modified epoxy resin is added after stirring for 10 minutes, leveling agent and defoaming agent are added after continuing to stir for 3 minutes, modified curing agent is added after stirring for 5 minutes, pigment is added after 5 minutes, stirring is continued for 10 minutes and the material is discharged; the prepared coating is scraped onto a metal substrate by a scraping technology, and the coating thickness is 1.0 mm; the coating is then cured in an oven at 80° C. for 10 hours to obtain the anti-concrete adhesion and corrosion-resistant coating.
[0082] In this example, the dispersant is one of triethylhexyl phosphoric acid and polyacrylamide, and the specific product models that can be used are: K-271, ZY-DP-1; the leveling agent adopts polyether modified polydimethylsiloxane solution, and the specific product models that can be used are: BYK-346, XYS-5313; the defoaming agent is an organic silicone complex, and the specific product models that can be used are: Z-2004, F-0103.
[0083] In addition, this example does not limit the content of the pigment.
[0084] Example 4
[0085] The anti-concrete adhesion and corrosion-resistant coating comprises the following raw materials in parts by mass:
[0086] 33 parts of modified epoxy resin, 11 parts of modified curing agent, 14 parts of filler, 5 parts of nanoparticles loaded with corrosion inhibitor, 1 part of leveling agent, 0.2 parts of defoaming agent, 0.4 parts of dispersant, 30 parts of solvent, and appropriate amount of pigment.
[0087] The epoxy resin modification operation is as follows: 6 g of bisphenol A epoxy resin is dissolved in 30 mL of ethyl acetate and magnetically stirred at 60° C. for 30 minutes, then 0.4 mL of 98% pure fluorine-free silane coupling agent and 0.08 mL of water are added, and the mixture is stirred at 60° C. for 6 hours to obtain a modified epoxy resin. The code name of the fluorine-free silane coupling agent used in this example is A172.
[0088] The curing agent modification operation is as follows: 10g of fatty amine curing agent is dissolved in 20mL of ethyl acetate and stirred magnetically at 80℃ for 45 minutes, then 0.5mL of 98% pure perfluoro organic acid C is added. n F 2n+1 COOH, react at 100°C for 4-6 hours under stirring to obtain a modified curing agent.
[0089] The corrosion inhibitor loading operation is as follows: 1g of corrosion inhibitor is dispersed in 10mL of DMF solution, magnetically stirred for 30min, and 1g of mesoporous silica nanoparticles is added. Subsequently, the DMF solution containing mesoporous silica nanoparticles is placed in a vacuum oven, vacuumed for 3h, and then placed under standard atmospheric pressure for 1h. This process is repeated three times to increase the loading amount of corrosion inhibitor in mesoporous silica nanoparticles. Finally, the solution obtained by repeating three times is centrifuged, washed, and dried at 60°C for 10h to obtain nanoparticles loaded with corrosion inhibitor.
[0090] The fillers are silicon carbide fiber, glass fiber, zirconium oxide, and white carbon black, wherein the mass ratio of glass fiber, silicon carbide fiber, zirconium oxide, and white carbon black is 3:2:4:1, and the size of the glass fiber is 20 μm, the size of the silicon carbide fiber is 30 μm, the size of the zirconium oxide is 30 nm, and the size of the white carbon black is 20 nm. The nanoparticles loaded with corrosion inhibitors are mesoporous silica nanoparticles loaded with sodium citrate and sodium tripolyphosphate, and the mass ratio of sodium citrate to sodium tripolyphosphate is 1:2. The solvent is prepared by mixing butyl acetate and cyclohexanone and then adding ammonia water with a mass fraction of 1%. The mass ratio of butyl acetate to cyclohexanone is 2.8:1.
[0091] The preparation method of the anti-concrete adhesion and corrosion-resistant coating is as follows: fillers, nanoparticles loaded with corrosion inhibitors, and dispersants are added to a high-speed stirring kettle, modified epoxy resin is added after stirring for 10 minutes, leveling agent and defoaming agent are added after continuing to stir for 3 minutes, modified curing agent is added after stirring for 5 minutes, pigment is added after 5 minutes, stirring is continued for 3 minutes and the material is discharged; the prepared coating is scraped onto a metal substrate by a scraping technology, and the coating thickness is 0.8 mm; the coating is then cured in an oven at 60° C. for 10 hours to obtain the anti-concrete adhesion and corrosion-resistant coating. Figure 2 It is characterized that the surface of the coating in this example is hydrophobic and the contact angle is 120°, indicating that the coating has a high hydrophobicity.
[0092] In this example, the dispersant is one of triethylhexyl phosphoric acid and polyacrylamide, and the specific product models that can be used are: K-271, ZY-DP-1; the leveling agent adopts polyether modified polydimethylsiloxane solution, and the specific product models that can be used are: BYK-346, XYS-5313; the defoaming agent is an organic silicone complex, and the specific product models that can be used are: Z-2004, F-0103.
[0093] In addition, this example does not limit the content of the pigment.
[0094] Example 5
[0095] The anti-concrete adhesion and corrosion-resistant coating comprises the following raw materials in parts by mass:
[0096] 36 parts of modified epoxy resin, 12 parts of modified curing agent, 20 parts of filler, 5 parts of nanoparticles loaded with corrosion inhibitor, 0.2 parts of leveling agent, 0.2 parts of defoaming agent, 0.4 parts of dispersant, 40 parts of solvent, and appropriate amount of pigment.
[0097] The epoxy resin modification operation is as follows: 10 g of bisphenol A epoxy resin is dissolved in 30 mL of ethyl acetate and magnetically stirred at 60° C. for 30 minutes, then 0.3 mL of 98% pure fluorine-free silane coupling agent and 0.08 mL of water are added, and the mixture is stirred at 60° C. for 7 hours to obtain a modified epoxy resin. The fluorine-free silane coupling agent used in this example is codenamed A171.
[0098] The curing agent modification operation is as follows: 10g of fatty amine curing agent is dissolved in 20mL of ethyl acetate and stirred magnetically at 80℃ for 45 minutes, then 0.6mL of 98% pure perfluoro organic acid C is added. n F 2n+1 COOH, react at 100°C for 6 hours under stirring to obtain a modified curing agent.
[0099] The corrosion inhibitor loading operation is as follows: 1g of corrosion inhibitor is dispersed in 10mL of DMF solution, magnetically stirred for 30min, and 1g of mesoporous silica nanoparticles is added. Subsequently, the DMF solution containing mesoporous silica nanoparticles is placed in a vacuum oven, vacuumed for 3h, and then placed under standard atmospheric pressure for 1h. This process is repeated three times to increase the loading amount of corrosion inhibitor in mesoporous silica nanoparticles. Finally, the solution obtained by repeating three times is centrifuged, washed, and dried at 60°C for 10h to obtain nanoparticles loaded with corrosion inhibitor.
[0100] The fillers are air glass microspheres, zirconium oxide, white carbon black and glass fibers, wherein the ratio of glass fibers, air glass microspheres, zirconium oxide and white carbon black is 2:1:3:2, the size of the glass fibers is 5 μm, the size of the air glass microspheres is 20 nm, the size of the zirconium oxide is 30 nm, the size of the white carbon black is 50 nm, the nanoparticles loaded with corrosion inhibitors are mesoporous silica particles loaded with sodium citrate, and the solvent is prepared by mixing cyclohexanone and ethyl acetate and then adding ammonia water with a mass fraction of 1%. The mass ratio of cyclohexanone to ethyl acetate is 2:1.
[0101] The preparation method of the anti-concrete adhesion and corrosion-resistant coating is as follows: fillers, nanoparticles loaded with corrosion inhibitors, and dispersants are added to a high-speed stirring kettle, modified epoxy resin is added after stirring for 10 minutes, leveling agent and defoaming agent are added after continuing to stir for 3 minutes, modified curing agent is added after stirring for 5 minutes, pigment is added after 5 minutes, stirring is continued for 4 minutes and the material is discharged; the prepared coating is scraped onto a metal substrate by a scraping technology, and the coating thickness is 0.9 mm; the coating is then cured in an oven at 80° C. for 2 hours to obtain the anti-concrete adhesion and corrosion-resistant coating. Figure 3 The figure shows the anti-adhesion to concrete. After the concrete hardens, it will naturally peel off from the coating without adhesion.
[0102] In this example, the dispersant is one of triethylhexyl phosphoric acid and polyacrylamide, and the specific product models that can be used are: K-271, ZY-DP-1; the leveling agent adopts polyether modified polydimethylsiloxane solution, and the specific product models that can be used are: BYK-346, XYS-5313; the defoaming agent is an organic silicone complex, and the specific product models that can be used are: Z-2004, F-0103.
[0103] In addition, this example does not limit the content of the pigment.
[0104] The present invention adopts modified epoxy resin, modified curing agent and filler to reduce the surface energy of the coating, improve the anti-sticking performance, mechanical durability, chemical stability and other properties of the coating; and adds nanoparticles loaded with corrosion inhibitor to achieve the continuous release of the corrosion inhibitor and improve the corrosion resistance of the coating.
[0105] Comparative Example:
[0106] Ordinary anti-concrete adhesion and corrosion-resistant coating: The coating is proportioned by mass as follows:
[0107] Epoxy resin 57 parts
[0108] 2.2 parts of curing agent
[0109] 36 parts of filler
[0110] 5 parts of general additives
[0111] 1 part carbon black
[0112] 30 parts solvent
[0113] All materials were added into a high-speed stirring kettle according to the above formula, and the materials were discharged after stirring for 30 minutes; the prepared coating was scraped onto the metal substrate by using a scraping technique; the coating was then cured in an oven at 60° C. for 6 hours to obtain an anti-adhesion and corrosion-resistant coating.
[0114] The surface hardness, corrosion resistance, contact angle, and concrete peeling cycle times of Examples 1-5 and the comparative example were measured and summarized in Table 1.
[0115] Table 1 Comparison table of various data of Examples 1-5 and Comparative Examples
[0116]
[0117] From the data in Table 1, it can be seen that the anti-concrete adhesion corrosion-resistant coating prepared by the present invention has the advantages of good anti-corrosion performance, high adhesion, excellent hydrophobic performance, a contact angle of more than 115 degrees, 60 concrete curing and demolding cycles, a coating hardness of more than 5H, no shedding of the coating after scratching, smooth cutting edges without shedding, etc., which greatly improves the performance of ordinary corrosion-resistant coatings.
[0118] The above are merely embodiments of the present application and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. Anti-concrete adhesion and corrosion resistant coating, characterized in that: Including the following raw materials in parts by weight: 30-50 parts of modified epoxy resin, 10-20 parts of modified curing agent, 10-20 parts of filler, 2-5 parts of nanoparticles loaded with corrosion inhibitor, 0.1-1 parts of leveling agent, 0.2-0.6 parts of defoaming agent, 0.2-0.6 parts of dispersant, and 30-50 parts of solvent.
2. The anti-concrete adhesion and corrosion-resistant coating according to claim 1, characterized in that: The modified epoxy resin is prepared by the following method: 6-10 g of bisphenol A epoxy resin is dissolved in 30 mL of ethyl acetate and magnetically stirred at 60° C. for 30 minutes, then 0.1-0.5 mL of a fluorine-free silane coupling agent with a purity of 98% and 0.05-0.1 mL of water are added, and the mixture is reacted at 60° C. for 6-8 hours under stirring to obtain the modified epoxy resin.
3. The anti-concrete adhesion and corrosion-resistant coating according to claim 1, characterized in that: The modified curing agent is prepared by the following method: 6-10g of aliphatic amine curing agent is dissolved in 20mL of ethyl acetate and magnetically stirred at 80°C for 45 minutes, then 0.3-0.6mL of a perfluoro organic acid with a purity of 98% is added, and the mixture is reacted at 100°C for 4-6 hours under stirring to obtain the modified curing agent.
4. The anti-concrete adhesion and corrosion-resistant coating according to claim 3, characterized in that: The chemical formula of the perfluoro organic acid is: n F 2n+1 COOH.
5. The anti-concrete adhesion and corrosion-resistant coating according to claim 1, characterized in that: The filler includes a micron-sized fibrous filler and a nano-sized filler in a mass ratio of 1:3-2:3; wherein the micron-sized fibrous filler is one or two of glass fiber and silicon carbide fiber, and the size of the micron-sized fibrous filler is 5-20 μm; the nano-sized filler is two or more of zirconium oxide, white carbon black, air glass microbeads, and diatomaceous earth, and the size of the nano-sized filler is 20-50 nm.
6. The anti-concrete adhesion and corrosion-resistant coating according to claim 1, characterized in that: The nanoparticles in the nanoparticles loaded with corrosion inhibitors are mesoporous silica nanoparticles, and the corrosion inhibitor is any one or two of sodium stannate, sodium citrate, sodium tripolyphosphate, carbon quantum dots, and cerium sulfate.
7. The anti-concrete adhesion and corrosion-resistant coating according to claim 6, characterized in that: The nanoparticles loaded with corrosion inhibitor are prepared by the following method: 1 g of corrosion inhibitor is dispersed in 10 mL of DMF solution, magnetically stirred for 30 minutes, 1 g of mesoporous silica nanoparticles is added, and then the DMF solution containing the mesoporous silica nanoparticles is placed in a vacuum oven for 3 hours, and then placed under standard atmospheric pressure for 1 hour; this process is repeated three times to increase the loading amount of corrosion inhibitor in the mesoporous silica nanoparticles; finally, the solution obtained by repeating three times is centrifuged, washed, and dried at 60° C. for 10 hours to obtain nanoparticles loaded with corrosion inhibitor.
8. The anti-concrete adhesion and corrosion-resistant coating according to claim 1, characterized in that: The solvent is prepared by adding 1%-4% ammonia water to a mixture of any two of butyl acetate, cyclohexanone and ethyl acetate, wherein the mass ratio of any two components in the solvent is 2:1-3:
1.
9. The anti-concrete adhesion and corrosion-resistant coating according to any one of claims 1 to 8, characterized in that: The coating also includes a pigment, and the surface hardness of the coating reaches 5-6H, the surface is hydrophobic and the contact angle is above 116°. In a laboratory cement curing peeling test, the adhesion area does not exceed 20% after 60 cycles, and the coating is immersed in concrete simulation liquid for 60 days without hollowing or falling off.
10. A method for preparing a corrosion-resistant coating that resists concrete adhesion, used for preparing the coating according to claim 9, characterized in that: The preparation method adopts the following operation process: (1) Add filler, nanoparticles loaded with corrosion inhibitor, dispersant and 1 / 3 of solvent into a high-speed stirring kettle, add modified epoxy resin and 1 / 3 of solvent after stirring for 10 minutes, add leveling agent and defoamer after continuing stirring for 3 minutes, add modified curing agent and 1 / 3 of solvent after continuing stirring for 5 minutes, add pigment after 5 minutes, continue stirring for 3-10 minutes and then discharge; (2) applying the coating prepared above onto a clean metal substrate using a scraper coating technique, with a coating thickness of 0.8-1.0 mm; (3) Curing the coating prepared above at 60-80° C. for 3-10 hours to obtain a concrete-adhesion and corrosion-resistant coating.
Citation Information
Patent Citations
Nano container loaded with corrosion response agent, preparation method and application thereof
CN111218144A
Organosilicon-modified epoxy resin anticorrosive paint
CN112592615A
Super-hydrophobic epoxy anticorrosive coating and preparation method thereof
CN115403991A
High-hydrophobicity CI-ZIF-8-coated DMBIM modified anticorrosive coating
CN117264499A
Reversible self-early-warning and self-repairing coating and preparation method thereof
CN117777820A